Study protocol to determine the effects of highly absorbable oral curcumin on the indicators of cognitive functioning: a double-blind randomised controlled trial. Issue 9 (19th September 2022) - Komiyama, Maki; Ozaki, Yuka; Wada, Hiromichi; Yamakage, Hajime; Satoh-Asahara, Noriko; Kishimoto, Atsuhiro; Katsuura, Yasuhiro; Imaizumi, Atsushi; Hashimoto, Tadashi; Sunagawa, Yoichi; Morimoto, Tatsuya; Hasegawa, Koji
Abstract : Introduction: Mild cognitive impairment (MCI) refers to a state in which cognitive functions, such as memory, have diminished but daily activities are largely unhampered. MCI is often overlooked but carries the risk of leading to development of dementia later. Curcumin is the main component of the natural herbal medicine turmeric. Curcumin is widely used as a health food and is an antioxidant that has anti-inflammatory and anti-amyloid actions. The current trial was designed to determine the effects of curcumin on indicators of cognitive functioning. Methods and analysis: The current trial will be a single-centre randomised placebo-controlled double-blind parallel group trial. The participants will be 60 members of the general public with potential MCI, based on dementia screening using the Japanese version of the Mini Mental State Examination (MMSE-J). The investigational health food used in this trial will be a recently developed preparation for highly absorbable oral curcumin. This trial will determine the effects of the highly absorbable oral curcumin (brand name: curcuRouge) on the indicators of cognitive functioning, including the scores obtained with the MMSE-J, which is an interview-based measure of cognitive functioning, and the blood biomarkers that have been reported to be associated with dementia. Ethics and dissemination: Informed written consent will be obtained from all the participants. The Ethical Review Board of the National Hospital Organization Kyoto Medical Center approved the study protocol. Trial registration number: University Hospital Medical Information Network (UMIN000042471).